2021
DOI: 10.1021/acs.jafc.1c00934
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Cross-Allergenicity of Tropomyosin from Freshwater Crustaceans

Abstract: Tropomyosin is a major allergen responsible for cross-allergenicity in a number of shellfish species. Although extensively characterized in marine crustaceans, the information of tropomyosin is limited to a few freshwater crustacean species. As a result, more cross-reactivity evidence and information of tropomyosin at the molecular level are required for the detection of freshwater crustaceans in the food industry. In this study, we explored tropomyosin allergenicity in four freshwater crustacean species: praw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…TM has largely been identified in invertebrates and vertebrates, and its sensitization was widely found in invertebrates, especially in shellfish. 12 As a pan-allergen in most species, 2,5 the identified TM in abalone could improve the understanding of allergens in shellfish. In this study, TM was purified and identified from H. discus hannai.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TM has largely been identified in invertebrates and vertebrates, and its sensitization was widely found in invertebrates, especially in shellfish. 12 As a pan-allergen in most species, 2,5 the identified TM in abalone could improve the understanding of allergens in shellfish. In this study, TM was purified and identified from H. discus hannai.…”
Section: ■ Discussionmentioning
confidence: 99%
“…At present, shellfish allergens have been widely identified, including tropomyosin (TM), arginine kinase, myosin light chain, sarcoplasmic calcium-binding protein, paramyosin, and filamin C, which could cause different degrees of sensitization. TM is a pan-allergen with high allergenicity in shellfish, which consists of two α-helical polypeptide subunits forming a stable coiled coil, whereas it typically exists as one subunit with a molecular weight of 32∼40 kDa in invertebrates. , However, TM with different subunits was gradually identified in shellfish, but the immunoreactivity differences of these subunits have not been fully elucidated. , Thus, a more extensive study of TM in H.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Molecular cloning is a successful technique to characterize protein nucleotides which can be encoded as AA. 20 The gene sequence of TM has been widely cloned in crustaceans with high conservation. 20 Nevertheless, there has been no report focusing on the gene sequence of TM in A. plicatula , and its AA sequence remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…20 The gene sequence of TM has been widely cloned in crustaceans with high conservation. 20 Nevertheless, there has been no report focusing on the gene sequence of TM in A. plicatula , and its AA sequence remains unclear. The lack of the primary sequence of ATM is not conducive to analyzing its conservation in molluscs.…”
Section: Introductionmentioning
confidence: 99%